PROFESIONALISME APARAT KELURAHAN DALAM PELAYANAN PUBLIK (Studi di Kelurahan Kameloh Baru Kecamatan Sabangau Kota Palangka Raya) - Ester Sonya Ulfaritha Lapalu; Imam Baihaqi (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2022)
There are many types of public services in the kelurahan which are still considered less than optimal by the apparatus, especially the apparatus of the Kameloh Baru Village, Sabangau Subdistrict, Palangka Raya City. There are so many problems that arise due to the lack of professionalism of the village apparatus towards public services which results in the community being dissatisfied. The purpose of this study was to find out and analyze how the professionalism of the village apparatus in public services in Kameloh Baru Village and to find out and analyze what dimensions affect public services in Kameloh Baru Village. In this study, the method used by the researcher is a qualitative data analysis method. The results of this study are in carrying out public services to the maximum with excellent and professional service for the urban village apparatus so that the community feels satisfied by applying good public services. Employee professionalism has a strong and positive influence on the quality of public services, with the result that the professionalism of the state civil apparatus has a strong and significant influence on service quality. This means that if the professionalism of the apparatus increases, the quality of public services produced will also increase. Likewise, if professionalism is very lacking, it will have an impact on service quality.